Peran Kepolisian dalam Menanggulangi Kejahatan Jalanan - Septian Parulian Manalu (Perspektif Administrasi Publik dan hukum, 2025)
Street crime is a conventional crime that occurs in public spaces and disturbs people's sense of security. The National Police of the Republic of Indonesia has an important role in dealing with this crime through preventive, preemptive, and repressive strategies. This article uses a descriptive qualitative approach based on a literature study. The results of the analysis show that the effectiveness of the police force is influenced by the availability of resources, community participation, and cross-sectoral coordination. Efforts such as Operation Cipta Condition have proven to be able to reduce the crime rate, but there are still obstacles such as a lack of personnel and technological facilities. Therefore, a multidimensional approach that involves the support of the government, the community, and strengthening the criminal justice system is key to tackling street crime effectively and sustainably.